Improvement of ferroelectric fatigue endurance in multiferroic (Ba(0.5)Sr(0.5))TiO(3)/(Bi(1.05)La(0.05))FeO(3)/(Ba(0.5)Sr(0.5))TiO(3) sandwich structures - Chew, Khian Hooi; Wang, Y.; Miao, J.; Zhang, B.P. (AIP Publishing, 2008)
We report the improved ferroelectric properties in dielectric/multiferroic/dielectric sandwich structures composed of Ba(0.5)Sr(0.5)TiO(3) (BST) and Bi(1.05)La(0.05)FeO(3) (BLF). Compared with the single BLF film, the trilayer structures exhibit a lower dielectric loss and weaker frequency dependence of dielectric properties. At room temperature, the remnant polarization and saturation polarization of the trilayer structures are 34.3 and 46.9 mu C/cm(2), respectively. More interestingly, the polarization of BST/BLF/BST trilayer exhibits a fatigue-free characteristic of up to 10(9) switching cycles. Applying Dawber's model, the concentration of oxygen vacancies and barrier energy of oxygen vacancies migration in BST/BLF/BST trilayer are calculated as 6.1x10(17) cm(-3) and 1.33 eV, respectively. (C) 2008 American Institute of Physics.